2015
DOI: 10.4314/ijbcs.v9i4.12
|View full text |Cite
|
Sign up to set email alerts
|

Equations allométriques pour l’estimation de la biomasse aérienne de <i>Faidherbia albida</i> (Del.) Achev dans les agrosystèmes d’Aguié, Niger

Abstract: Cette étude a été conduite dans la zone sahélienne à Aguié (Niger) avec l'objectif d'élaborer des modèles allométriques d'estimation de la biomasse aérienne de Faidherbia albida dans les agrosystèmes. La méthode directe servant à abattre et peser compartiment par compartiment la biomasse à l'aide des échantillons d'arbre est utilisée. Deux types de modèle ont été testés : le modèle puissance (y = ax b) et le modèle polynomial (y = a + bx + cx 2 et y = a + bx + cx 2 + dx 3) avec y la biomasse aérienne totale ; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…R 2 > 0.65) for all tree components in the two climatic zones. This type of equation is widely reported by many authors in the tropical zones of Africa ( Henry et al., 2011 ; Antin et al., 2013 ; Laminou Manzo et al., 2015 ; Xiang et al., 2016 ; Dimobe et al., 2018 ; Mensah et al., 2018 ). In addition, the power models are simple and practical in estimating the biomass of several woody species, and this fact lead several authors to prefer them than polynomial and logarithmic equations that have high elasticity ( Xiang et al., 2016 ; Yuen et al., 2016 ).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…R 2 > 0.65) for all tree components in the two climatic zones. This type of equation is widely reported by many authors in the tropical zones of Africa ( Henry et al., 2011 ; Antin et al., 2013 ; Laminou Manzo et al., 2015 ; Xiang et al., 2016 ; Dimobe et al., 2018 ; Mensah et al., 2018 ). In addition, the power models are simple and practical in estimating the biomass of several woody species, and this fact lead several authors to prefer them than polynomial and logarithmic equations that have high elasticity ( Xiang et al., 2016 ; Yuen et al., 2016 ).…”
Section: Discussionmentioning
confidence: 59%
“…Therefore there is an increasing interest to convince policy makers of the need for tools to assess plants ability to capture and store the atmospheric carbon (C). There is also a necessity to set reliable, accurate and economical methods for estimating the biomass of trees and shrubs ( Djomo et al., 2010 , 2016 ; Laminou Manzo et al., 2015 ). These tools would help to determine the geographical distribution of C stocks and to understand changes in C stocks in relation to other parameters such as land use and climatic zones.…”
Section: Introductionmentioning
confidence: 99%
“…The best prediction models are the second order polynomial allometric equation and the linear equation. Furthermore, the work of [26] [27] [29] and [43] have shown that a model can have a high coefficient of determination, meet all preliminary tests (p-value > 0.05) and be subsequently rejected by the assessment of certain validation criteria, notably the different statistical tests, standard residual error, Akaike information criterion (AIC).…”
Section: Discussionmentioning
confidence: 99%
“…Te estimation model (M5b) for the total biomass presents a coefcient of determination (adjusted R 2 ) greater than 0.94, and the value of the AIC and the RSE low but has not been validated by the various tests in occurrence the Breusch-Pagan test or the value of the statistic is less than 0.05. A model can have a high coefcient of determination and the residual standard error (RSE) and the Akaike information criterion (AIC) low and be rejected by the assessment of certain validation criteria, and in particular, the diferent statistical tests [32,33,43]. Te ratio of belowground biomass to aboveground biomass (BGB/ AGB) gives a ratio of 0.22 which is close to the ratio of 0.24 proposed by the IPCC [35].…”
Section: Discussionmentioning
confidence: 74%